Spectral Monitoring CH/C2 Ratio of Methane Plasma for Growing Single-Layer Graphene on Cu. (1st July 2015) - Chan, Shih-Hao; Liao, Shih-Fang; Chen, Hung-Pin; Wei, Hung-Sen; Chen, Sheng-Hui; Lee, Cheng-Chung; Kuo, Chien-Cheng
Abstract : Single-layer graphene was grown on copper at a low temperature of 600°C by plasma-assisted thermal chemical vapor deposition. Its growth mechanism was discussed with reference to the emission spectra of the plasma. The methane plasma produces the active species (H x, CH x, and C x ) without the addition of flowing hydrogen, and the amounts of hydrogen-containing species can be controlled by varying the plasma power. The effective distance was found between the plasma initial stage and the deposition stage for the single-layer graphene synthesis. The results reveal that high-quality graphene can be synthesized using methane plasma at a suitable plasma power.